Effect of Firm Characteristics and Some Key Monetary Variables on the Financial Performance of Unilever Nigeria Plc - Ahmad, Zubairu; Hassan, Adamu; Dakingari, Usman Muhammad (Asian Journal of Economic Modelling, 2022)
The purpose of this paper is to examine the influence of firm characteristics and some key monetary variables on the financial performance of Unilever Nigeria Plc. The variables used are financial performance, capital structure, dividend policy, managerial efficiency, inflation rate, interest rate and exchange rate. The autoregressive distributive lag (ARDL) model was used for the study. The findings show that capital structure and managerial efficiency have a significant positive effect on the financial performance of the sampled company; however, dividend policy has no significant influence on the financial performance of the company. Similarly, from the key monetary variables aspect, the study discovered that inflation rate and exchange rate have a significant positive influence on the financial performance of the company, while interest rate has a significant negative effect on the company’s financial performance. Based on these, this study suggests the need for the company to increase its effort to improve its capital structure and managerial efficiency. In addition, the study suggests the need for the company to consider the volatility of inflation and exchange rate when making investment decisions. Finally, the lending rate should be reduced by the deposit money banks for the company to gain easy access to capital to increase its investments and financial performance.